2020
DOI: 10.3390/w12123400
|View full text |Cite
|
Sign up to set email alerts
|

Testing Different Membrane Filters for 16S rRNA Gene-Based Metabarcoding in Karstic Springs

Abstract: Introduction: Karstic springs are used worldwide by rural communities as sources of fresh water for humans and livestock. In Romania, one-third of the population has no direct access to a public water supply. The present study is part of a country-wide project to develop simple, quick and cheap methods for seasonal environmental and microbiological monitoring of karstic springs used as drinking water by rural populations. Critical steps for monitoring workflow consist of evaluating water quality and selecting … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…A similar spatial variation pattern was noticed also for the TDS, with values ranging between 131 and 1092 mg L −1 , the highest values being recorded in the southern region and the lowest in the middle region of the studied area. The spatial variation of the EC and TDS may reflect the wide variation in the anthropic activities and natural processes in the studied region, and also the dilution effects-due to the groundwater recharging from the Aries and Somesul Mic rivers [42][43][44][45].…”
Section: Spatial Distribution Of Groundwater Chemistrymentioning
confidence: 99%
“…A similar spatial variation pattern was noticed also for the TDS, with values ranging between 131 and 1092 mg L −1 , the highest values being recorded in the southern region and the lowest in the middle region of the studied area. The spatial variation of the EC and TDS may reflect the wide variation in the anthropic activities and natural processes in the studied region, and also the dilution effects-due to the groundwater recharging from the Aries and Somesul Mic rivers [42][43][44][45].…”
Section: Spatial Distribution Of Groundwater Chemistrymentioning
confidence: 99%
“…The number of inhabitants that use GW3 and GW4 as drinking water sources are 3-fold higher, while the flow rates are one order of magnitude lower than of GW1 and GW3. The human induced alteration of the groundwater flow by intensive usage in the case of GW3 and GW4 might contribute to the increase of pollutants concentration and water quality decline of these springs by the mobilization of naturally occurring trace elements from the aquifer materials through which the water flows [33].…”
Section: Description Of the Study Areamentioning
confidence: 99%
“…The health risk assessment data based on water chemistry indicated that the studied springs could be used by the local communities as drinking water supply but only after the microbiological quality assessment as well as water treatment and disinfection [ 43 , 44 ]. The regular water quality monitoring could be a preventive measure that will identify any possible contamination.…”
Section: Resultsmentioning
confidence: 99%